Consensus Statement on the Use of Bone Turnover Markers for Short-Term Monitoring of Osteoporosis Treatment in the Asia-Pacific Region - Wu, Chih-Hsing; Chang, Yin-Fan; Chen, Chung-Hwan; Lewiecki, E Michael; Wüster, Christian; Reid, Ian; Tsai, Keh-Sung; Matsumoto, Toshio; Mercado-Asis, Leilani B; Chan, Ding-Cheng; Hwang, Jawl-Shan; Cheung, Ching-Lung; et al. (Journal of clinical densitometry, 2021)
Osteoporosis is a major health issue. By 2050, a greater than 2-fold increase in patients number with hip fractures will occur in Asia representing 50% of all hip fractures worldwide. For the Asia-Pacific (AP) region, more efforts on controlling osteoporosis and the subsequent fractures are crucial. Bone mineral density (BMD) by dual energy X-ray absorptiometry (DXA) is commonly used to diagnose osteoporosis and monitor osteoporosis treatment. However, the inconvenience, cost, limited availability of DXA and the delay in detection of BMD changes after treatment initiation support an important role for bone turnover markers (BTMs), as short-term tools to monitor therapy. With regards to low adherence rates of medical treatment of osteoporosis, the experts reached consensus on the use of BTMs for both raising awareness and short-term monitoring of osteoporosis treatment in the AP region. The experts endorse the use of BTMs, especially serum C-terminal telopeptide of type 1 collagen (CTX) and serum procollagen type 1 N propeptide (P1NP), as short-term monitoring tools to help clinicians assess the responses to osteoporosis therapies and appropriately adjust treatment regimens earlier than BMD. Either the absolute values or the degree of change from baseline in BTMs can be used to monitor the potential efficacy of osteoporosis therapies. The use of BTMs can be incorporated in osteoporosis care programs, such as fracture liaison service (FLS), to improve patient adherence and treatment outcomes. Encouraging sufficient reimbursement from health care systems may facilitate widespread use of BTMs in clinical practice in the AP region.